Prijateljstvo u kasnosrednjovjekovnoj dubrovačkoj političkoj misli i svakodnevnici - Šoštarić, Valentina (2026)
The monograph addresses political friendship in late medieval Dubrovnik as a multi-layered phenomenon operating simultaneously within political thought and everyday social practices. Its central premise is that the boundary between the private and public spheres was not clearly defined, as personal relationships constituted an integral component of political action. Friendship encompassed mutual assistance, advice, and economic support, but also moral obligations and emotional patterns that shaped the behavior of participants. It therefore did not refer exclusively to a private or affective bond, but to a socially, politically, and legally recognized relationship grounded in reciprocity and expected norms of conduct.            In the late medieval context, friendship carried a significantly broader meaning than in contemporary usage. It included kinship and marital ties, relations of dependency, clientelist networks, military and professional associations, guilds, confraternities, and various institutional and private forms of networking. This semantic breadth enabled its application across both horizontal and vertical relations within the sphere of high politics, where friendship networks functioned as an important instrument for access to resources of power, career advancement, and political stability.            A key contribution of the study lies in its analysis of the discourse of (non-)friendship, which served as a performative tool. The authorities of Dubrovnik employed the language of friendship and enmity as a means of shaping social and political reality. To label someone as a “friend” was to establish a relationship implying mutual assistance and loyalty, whereby language directly influenced the behavior of actors and guided political action, particularly in contexts of uncertainty.            Moral values occupied a central place in the functioning of these relationships. Loyalty, reliability, gratitude, steadfastness, and mutual trust were not abstract ideals, but concrete criteria of political credibility. Their fulfilment ensured the stability of relationships, while their violation, through betrayal, manipulation, or the withholding of support, led to loss of reputation and honor, the dissolution of alliances, and political isolation.            The emotional dimension of these relations played an equally pervasive role, particularly love, while hatred and jealousy could have both destructive and, at times, connective functions, depending on the context. Friendship and enmity were therefore not strictly separated categories, but fluid and mutable forms of relationship that could be transformed in accordance with changing circumstances. Neutrality, in turn, only gradually emerged as a third option and as a legally recognized category.            Symbolic practices were crucial for the confirmation and maintenance of friendship. Gestures of closeness, such as dining together, handshakes, embraces and kisses, gift-giving, shared riding, as well as public ceremonial rituals and oaths, served as visible expressions of commitment and reinforced social bonds. Nevertheless, such relationships remained vulnerable to disruption due to political realignments, where pragmatic considerations often overrode expected obligations.            In conclusion, political friendship in late medieval Dubrovnik functioned as a fundamental principle in the organization of socio-political structures, operating both at the level of central institutions of power and within individual lives. It integrated moral norms, emotional patterns, and pragmatic interests, serving not only as a means of achieving political objectives, but also as a mechanism for constructing personal and collective identities, legitimizing authority, and maintaining a balance between conflict and cooperation. Dubrovnik thereby fits within the broader context of the Latin West, confirming friendship as a universal yet adaptable category of medieval political culture. This study ultimately opens space for further reflection on social networking and relational practices, both in historical contexts and in contemporary society.